On factors affecting coalbed gas content measurement. (June 2018) - Long, Qingming; Hu, Qianting; Zhang, Zhenyu; Ren, Ting
Highlights: Small coal particles show high desorption rate at early stage of desorption. A critical coal particle size exists in methane desorption in coal. Coal article size distribution tends to be stable with coal sample mass over 15 g. Abstract: Coalbed gas content measurement is important for both unconventional gas recovery and mining safety. This study experimentally discussed factors affecting coalbed gas content measurement. It is found that small coal particles demonstrated high desorption rate at the early stage of desorption tests. However, the difference in methane desorption rate reduces when the coal particle size is more than 1.0 mm, indicating that a threshold of coal particle size exists in methane desorption in coal. Also, the particle size distribution tends to be stable when coal sample mass is over 15 g, stabilizing at around 1.75 mm. Therefore, the coal sample over 15 g is recommended to use in desorption tests of coalbed gas content measurement. The temperature and gas pressure can enhance the desorption rate, especially at the early stage of desorption. This temperature effect, however, mainly occurred in the first 15 min of desorption test. After 30 min, the desorption rate tends to be stable, slightly changing from around 0.35 mol/kg/min to 0.75 mol/kg/min. Due to endothermic process, absolute isothermal condition does not exist in desorption test, but this temperature variation mainly occurred in the first 15 min. The results also show incorporating the desorption data from the time of exposure to 13 min of desorption tests is essential to typically reflect methane desorption kinetics in coal. The study also shows that the measurement difference in gas content between the case with sample being air-puffed and -flushed and the case with sample exposed to the air is small. Therefore, the air-puffing and flushing during the sample collection has an insignificant effect the gas contact measurement result. This study can help to advance the understanding of impact factors on coalbed gas content measurement method.